Effect of design thinking training program on nurse managers' awareness and innovative managerial skills - Hany Salah Hussein Abo-Ramadan; Fatma Ahmed Abed; Lamia Mohamed-Nabil Ismail (2025)
Background: Enhancing nurse managers' awareness and innovation through design thinking is critical for advancing healthcare leadership and improving patient outcomes. Aim: To evaluate the effect of design training program on nurse managers awareness and innovative managerial skills. Design: Quasi-experimental design was utilized in this study. Setting: The study was conducted at the National Heart Institute. Subjects: A convenient sample of nurse managers (n = 30). Tools: Three tools were utilized: (1) Background data sheet including: (a) Socio-demographic data such as age, gender and (b) Personal characteristics such as educational level, years of experience, place of work; (2) Design thinking awareness assessment questionnaire (25 items); and (3) Innovative managerial skills checklist (42 items). Results: Revealed a highly statistically significant improvement in design thinking knowledge across program phases, as demonstrated by ANOVA (F= 23.32, P= 0.00) and Chi-square analysis ((S{(B2= 29.57, P= 0.00). While a slight decline in knowledge was observed during the follow-up phase, levels remained above the baseline. Additionally, the innovative managerial skills of nurse managers significantly improved, with mean percentages reaching satisfactory levels of 90% post program and 76.3% at follow-up, compared to an unsatisfactory preprogram baseline. Conclusion: The program effectively enhanced nurse managers$1 (Bknowledge and innovative managerial skills, demonstrating its value in improving managerial competencies in healthcare settings. Recommendations: Academic institutions should incorporate design thinking methodology into their nursing education programs.s
(3GdNdajI(B: (3ojYO JYRjR hYj eOQGA GdJeQjV hGHJcGQge ef NdGd GdJacjQ GdJUejej CekQG HGdZ GdCgejI ddfghV HGdbjGOI aj eLGd GdQYGjI GdUMjI hJMSjf fJGFL GdeQVi(B.(3GdgOa(B: (3Jbjje JCKjQ HQfGeL JOQjHj Yf GdJacjQ GdJUejej Ydi hYj eOQGA GdJeQjV hegGQGJ GdEOGQI GdGHOGYjI(B.(3GdJUeje(B: (3Je GSJNOGe GdJUeje THg GdJLQjHj aj gPg GdOQGSI(B.(3GdecGf(B: (3oCLQjJ GdOQGSI aj GdeYgO Gdbhej ddbdH(B.(3GdeTGQchf(B: (3YjfI edGFeI ef eOjQj GdJeQjV (B((3f (B= 30).(3GdCOhGJ(B: (3Je GSJNOGe KdGK COhGJ(B: (3GSJeGQI GdHjGfGJ GdCSGSjI GdJj JTed(B: ((3C(B) (3GdHjGfGJ GdGLJeGYjI hGdOjehZQGajI eKd GdYeQ hGdLfS, h(B((3H(B) (3GdNUGFU GdTNUjI eKd GdeSJhi GdJYdjej, hSfhGJ GdNHQI, hecGf GdYed(B. (3GSJHjGf Jbjje GdhYj HGdJacjQ GdJUejej (B(25 (3HfkOG(B). (3bGFeI eQGLYI GdegGQGJ GdEOGQjI GdeHJcQI (B(42 (3HfkOG(B).(3GdfJGFL(B: (3cTaJ GdfJGFL Yf JMSf Pj OdGdI EMUGFjI YGdjI aj GdeYQaI HGdJacjQ GdJUejej YHQ eQGMd GdHQfGeL(B. (3hbO Je EKHGJ Pdc ef NdGd JMdjd GdJHGjf (B(ANOVA) (3hJMdjd eQHY cGj (B(Chi-square) (3haj Mjf dhMX GfNaGV Waja aj eSJhi GdeYQaI NdGd eQMdI GdeJGHYI, EdG Cf GdeSJhjGJ XdJ CYdi ef NW GdCSGS (B((3GdeSJhi GdChdj(B). (3HGdEVGaI Edi Pdc, JMSfJ GdegGQGJ GdEOGQjI GdGHOGYjI deOQGA GdJeQjV HTcd edMhX, MjK hUdJ eJhSWGJ GdfSH GdeFhjI Edi eSJhjGJ oeQVjI HdZJ (B90% (3HYO GdHQfGeL h (B76.3% (3aj eQMdI GdeJGHYI, ebGQfI HNW CSGS ZjQ oeQmV bHd GdHQfGeL(B.(3GdGSJfJGL(B: (3YRR GdHQfGeL HaYGdjI eYQaI eOQGA GdJeQjV hegGQGJge GdEOGQjI GdGHOGYjI, eeG jOd Ydi bjeJg aj JMSjf GdegGQGJ GdEOGQjI aj HjFGJ GdQYGjI GdUMjI(B.(3GdJhUjGJ(B: (3jLH Ydi GdeDSSGJ GdCcGOjejI OeL efgLjI GdJacjQ GdJUejej aj HQGeLgG GdJYdjejI ddJeQjV(B.s
Thesis (Ph.D)-Cairo University, 2025.
Bibliography: pages 113-126.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Nursing Administration; (3EOGQI GdJeQjVs; Design thinking -- innovative managerial skills -- nurse managers -- (3eOQGA GdJeQjVs -- (3GdJacjQ GdJUejejs